Association between intraoperative hyperglycemia/hyperlactatemia and acute kidney injury following on-pump cardiac surgery: a retrospective cohort study - He, Qiyu; Tan, Zhimin; Chen, Dongxu; Cai, Shuang; Zhou, Leng (Frontiers in Cardiovascular Medicine, 2023)
Background: Despite the long-lasting notion about the substantial contribution of intraoperative un-stabilization of homeostasis factors on the incidence on acute kidney injury (AKI), the possible influence of intraoperative glucose or lactate management, as a modifiable factor, on the development of AKI remains inconclusive.To investigated the relationship between intraoperative hyperglycemia, hyperlactatemia, and postoperative AKI in cardiac surgery.Methods: A retrospective cohort study was conducted among 4435 adult patients who underwent on-pump cardiac surgery from July 2019 to March 2022. Intraoperative hyperglycemia and hyperlactatemia were defined as blood glucose levels >10 mmol/L and lactate levels >2 mmol/L, respectively. The primary outcome was the incidence of AKI. All statistical analyses, including t tests, Wilcoxon rank sum tests, chi-square tests, Fisher's exact test, Kolmogorov-Smirnov test, logistic regression models, subgroup analyses, collinearity analysis, and receiver operating characteristic analysis, were performed using the statistical software program R version 4.1.1.Results: Among the 4435 patients in the final analysis, a total of 734 (16.55%) patients developed AKI after on-pump cardiac surgery. All studied intraoperative metabolic disorders was associated with increased AKI risk, with most pronounced odds ratio (OR) noted for both hyperglycemia and hyperlactatemia were present intraoperatively (adjusted OR 3.69, 95% confidence intervals [CI] 2.68-5.13, p<0.001). Even when hyperglycemia or hyperlactatemia was present alone, the risk of postoperative AKI remained elevated (adjusted OR 1.97, 95% CI 1.50-2.60, p<0.001).The presence of intraoperative hyperglycemia and hyperlactatemia may be associated with postoperative acute kidney injury (AKI) in patients undergoing onpump cardiac surgery. Proper and timely interventions for these metabolic disorders are crucially important in mitigating the risk of AKI.